Law and culture in Japan: institutions, justice, and media - Deflem, Mathieu; Takahashi, Hiroshi; Vanoverbeke, Dimitri; Karlin, Jason G. (Sociology of crime, law and deviance, 2025)
Volume 30 of Sociology of Crime, Law and Deviance brings together scholars from various disciplinary backgrounds to discuss a variety of aspects and developments related to law and culture in contemporary Japan. Some scholars have law as their primary field of study and from that viewpoint focus on connections with culture, while others are first and foremost scholars of culture who link their research themes to norms and regulations. The interconnection between law and culture in Japanese society is the central substantive focus of the book. Thematically linked, the chapters are diverse in terms of theory, methodology, and (multi-)disciplinary perspective, discussing institutions of law, crime and justice, and various media. Written by expert scholars who work in Japan, Law and Culture in Japan communicates research on law and culture in Japanese society to a broad audience. This edited volume is essentially oriented at scholars and students who are located outside of Japan, yet who share similar scholarly interests in law, culture, and the interconnections between them.